Sistem Penyaliran Tambang dalam Menanggulangi Air Limpasan Alami dan Air Limpasan Terganggu di Open Channel Pit II Blok Utara PT. Tamarona Mas Internasional - Eko Chandraleksmana; Murad Murad (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. High rainfall at the planned mine site can hamper mining operations in achieving the production target of 500,000 MT/year. Planning of a mine drainage system is needed which is well reviewed technically and also the costs arising from the making of the mine drainage system. Analysis of daily rainfall data at the research location in 2010-2019 using gumbel distribution, obtained rainfall plan of 138.26 mm/day for the 5- year return period. After an analysis of the influential rain catchment area, a location that requires open channels and sewers was obtained. There are still dimensions of open channels and sewers that are not in accordance with the area of rain catchment that is influential based on the results of calculations. Excessive sedimentation in the sewer inlet occurs due to material conditions in the research area dominated by erosioneasily eroded sediment material and an open channel slope of >3% at the upstream. Avalanche on the open channel wall occurs because the material on the open channel wall is weak material and easily affected by water. In addition, the slope dimension of the wall is too steep (more than 60o ) also affects the avalanche that occurred. Excessive sedimentation in the inlet of sewers can be minimized by making a drop structure design and flow breaker structure while avalanches on open channel walls can be minimized by making the slope dimensions of open channel walls > 60o .Keyword: Production, Rainfall, Open channels, Culvert, Sedimentation